THE EFFECT OF EDUCATION ON STUDENTS' KNOWLEDGE AND BEHAVIOUR ABOUT HEALTHY SNACKS AT SDN MERGOSONO 3 IN MALANG CITY - Agustin, Adelia Putri Dwi; Saputra, Dimas Dwi Yoga; Suharno, Budi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Children often buy food outside and do not pay attention to hygiene and the content of the food. Based on a survey by the Food and Drug Administration, more than 99% of children consume snacks while at school. This high percentage allows the risk of health problems in children to be greater. The aim of the study was to identify the effect of education on students' knowledge and behaviour about healthy snacks. This research method is a quantitative method with a pre-experimental one group pre-test post-test research design. Sample determination using purposive sampling with a total of 30 respondents. The results of the study, the pretest knowledge of 13 students 43.3% good category, 17 students 56.7% sufficient category. After education, the results increased to 30 students 100% in the good category. Whereas in the results of behaviour before being given education (pretest) in the positive category none of the respondents behaved positively and negative behaviour of all 30 respondents 100%, behaviour after education (posttest) in the positive category increased to 100%. Hypothesis testing using the Wilcoxon Test with a knowledge value sign of 0.000 where (p < 0.05) and a behaviour value sign of 0.000 where (p < 0.05) so that it can be said that there is an increase in knowledge and behaviour after education to students about healthy snacks. It can be concluded that education is effective in improving students' knowledge and behaviour about healthy snacks.